Effect of grazing land exclosure and feeding strategy on livestock water productivity in Lencha Dima Watershed, Guba Lafto Woreda, Amhara Region - Mekonnen, S. (Hawassa University, 2009)
The study aims to estimate the livestock water productivity (LWP) and to examine the effect of grazing area closure and feeding strategies on LWP at farm household level under wealth and intervention categories at Lencha Dima watershed. Results are based on survey of 120 sample households and focus group discussion. Beneficial outputs of livestock and depleted water for producing them were estimated then livestock water productivity as the ratio of the beneficial out puts and depleted water was estimated. LWP shows difference between participant with in the interventions and non participant with the intervention farm households. The value of LWP in ETB was 1.7±0.3 in non participant farm household and 0.79±0.03 in participant farm household and it ranges from 1.7 at better off non participant farm household to 0.7 in very poor participant farm households. The highest livestock feed financial water productivity was estimated at very poor non participant farm households (5.5± 2.3 ETB m-3 per year). Crop residue accounted much in depleted water for livestock feed production and it is also the major contributor for livestock feed resource base, which were found at negative feed balance to the existing livestock holding at household and watershed level. To mitigate this shortage framers use different feeding strategies according to livestock importance and age. Much of the beneficial output valued at the present LWP accounted by traction and transport services and ranked as the primary purpose of cattle. Exclosure can improve the condition of degraded land and can also be used as source of income generation and source of wood for different purposes. But it has negative effect on livestock number, which are at low production level and it is difficult to conclude the effect of area closure on LWP and livestock productivity in short period of time. Strategy of improving livestock productivity through improved feed availability and quality together with livestock management and health care as well as water saving and conservation is crucial for lifting up benefits from livestock and LWP for the farm households. added